The significance of phase reversion-induced nanograined/ultrafine-grained (NG/UFG) structure on the strain hardening behavior and deformation mechanism in copper-bearing antimicrobial austenitic stainless steel. (July 2021) - Dong, H.; Li, Z.C.; Somani, M.C.; Misra, R.D.K.
Abstract: The unique concept of phase reversion involving severe deformation of parent austenite into martensite, followed by annealing for a short duration, whereby the strain-induced martensite reverts to austenite, was adopted to obtain nano-grained/ultrafine-grained (NG/UFG) structure in a Cu-bearing biomedical austenitic stainless steel resulting in high strength-high ductility combination. Work hardening and accompanying deformation mechanism are two important aspects that govern the mechanical behavior of biomedical devices. Thus, post-mortem electron microscopy of the strained region was carried out to explore the differences in the deformation mechanisms induced by grain refinement, while the strain hardening behavior was analyzed by Crussard-Jaoul (C-J) analysis of the tensile stress-strain data. The strain hardening behavior consisted of four stages and was strongly affected by grain structure. Twinning-induced plasticity (TWIP) was the governing deformation mechanism in the NG/UFG structure and contributed to good ductility. In striking contrast, transformation-induced plasticity (TRIP) contributed to high ductility in the coarse-grained (CG) counterpart and was the governing strain hardening mechanism. When the grain size is less than ~1 μm, the increase in the strain energy and the austenite stability significantly reduce the possibility of strain-induced martensite transformation such that there is a distinct transition in deformation mechanism from nanoscale twinning in the NG/UFG structure to strain-induced martensite in CG structure. The differences in the deformation mechanisms are explained in terms of austenite stability – strain energy relationship.